Kazal-type serine proteinase inhibitors in the midgut of Phlebotomus papatasi - Sigle, Leah Theresa; Ramalho-Ortigão, Marcelo (My University, 2013)
Sandflies (Diptera: Psychodidae) are important disease vectors of parasites of the genus Leishmania, as well as bacteria and viruses. Following studies of the midgut transcriptome of Phlebotomus papatasi, the principal vector of Leishmania major, two non-classical Kazal-type serine proteinase inhibitors were identified (PpKzl1 and PpKzl2). Analyses of expression profiles indicated that PpKzl1 and PpKzl2 transcripts are both regulated by blood-feeding in the midgut of P. papatasi and are also expressed in males, larva and pupa. We expressed a recombinant PpKzl2 in a mammalian expression system (CHO-S free style cells) that was applied to in vitro studies to assess serine proteinase inhibition. Recombinant PpKzl2 inhibited α-chymotrypsin to 9.4% residual activity and also inhibited α-thrombin and trypsin to 33.5% and 63.9% residual activity, suggesting that native PpKzl2 is an active serine proteinase inhibitor and likely involved in regulating digestive enzymes in the midgut. Early stages of Leishmania are susceptible to killing by digestive proteinases in the sandfly midgut. Thus, characterising serine proteinase inhibitors may provide new targets and strategies to prevent transmission of Leishmania.
Citation: Sigle, Leah Theresa, and Marcelo Ramalho-Ortigao. 2013. “Kazal-Type Serine Proteinase Inhibitors in the Midgut of Phlebotomus Papatasi.” Memórias Do Instituto Oswaldo Cruz 108 (6): 671–78. https://doi.org/10.1590/0074-0276108062013001.
Keywords: Diptera; Sandflies; Phlebotomus papatasi; Kazal-type inhibitors; Midgut; Blood meal digestion